The Meaning of Coming Out: From Self-Affirmation to Full Disclosure - Guittar, Nicholas A. (Qualitative Sociology Review, 2013)
Qualitative researchers have begun to analyze narratives of individuals’ experiences with coming out in order to explore the social influences that affect these processes. However, most studies on coming out are based on the assumption that “coming out” has a singular shared meaning. The present study is centered on challenging this very assumption by taking a constructivist grounded theory approach to exploring the meaning of coming out for 30 lesbian, gay, bisexual, and queer (LGBQ) individuals via open-ended interviews. Coming out does not have a universal meaning among LGBQ persons; rather, it varies on the basis of individuals’ experiences, social environment, and personal beliefs and values. All 30 participants in the current study agree that coming out is a transformative process and an important element in identity formation and maintenance, thus challenging the notion that coming out is no longer a relevant concept. For some participants coming out is more of a personal journey of self-affirmation, while for others it is about the sharing of their sexuality with others – and oftentimes a combination of these two characteristics. Implications for future research on coming out are included.